Control of fast electron propagation in foam target by high-Z doping. (4th January 2019) - Xu, H; Yang, X H; Liu, J; Borghesi, M
Abstract: The influence of high-Z dopant (bromine) in low-Z foam (polystyrene) target on laser-driven fast electron propagation is studied by the 3D hybrid particle-in-cell (PIC)/fluid code HEETS. It is found that the fast electrons are better confined in doped targets due to the increasing resistivity of the target, which induces a stronger resistive magnetic field which acts to collimate the fast electron propagation. The energy deposition of fast electrons into the background target is increased slightly in the doped target, which is beneficial for applications requiring long distance propagation of fast electrons, such as fast ignition.